Assessment of GCS and FOUR Score as Prognostic Indicators for Hospital Stay and Morbidity in Traumatic Brain Injury Patients: An Observational Study - K V Anand; P T Shahid; K K Shameel (Wolters Kluwer Medknow Publications, 2024)
Aim: The objective of the present research was to evaluate variations in hospital stay as well as morbidity based on the Glasgow Coma Scale (GCS) and Full Outline of Un-Responsive (FOUR) scores for patients who had traumatic brain injury (TBI). Materials and Methods: A total of 107 patients with TBI patients who attended the emergency department of MES Medical College, Perinthalmanna, were enrolled into the study. FOUR and GCS scoring systems were used to assess the patients within 24 hours of the presentation to the emergency department. Both FOUR and GCS scoring systems were assessed at the same time. The outcome was measured in terms of length of hospital stay and morbidity, which was assessed using modified Rankin score. Chi-square test was used to calculate sensitivity, specificity, positive predictive value, and negative predictive value. The area under the curve (AUC) was calculated using receiver operating characteristic curve analysis. A P value <0.05 was considered significant. Results: We found a strong positive correlation between GCS and FOUR score with a Spearman coefficient of 0.9. Comparison of AUC between GCS score and FOUR score showed a statistically significant difference (P = 0.0044), predicting that FOUR score was a better predictor of hospital stay (>15 days) than GCS score. Comparison of AUC between GCS score and FOUR score showed a significant statistical difference (P = 0.0002), showing that FOUR score was a better predictor of morbidity than GCS. Conclusion: FOUR score was a better predictor of hospital stay and morbidity as compared to GCS score.